Preserving source-location privacy efficiently based on attack-perceiving in wireless sensor network - Qian ZHOU; Xiaolin QIN; Youwei DING (Tongxin xuebao)
Sensors’ ability was utilized to perceive the mobile attacker nearby,and SPA (silent-pool approach) was proposed,which was able to hinder or reduce the packets hunted by the attacker by controlling the forwarding state of the nodes.In addition,a novel DPIOP (dummy packet injection out pool) method was proposed to entice the adversary far away from the transmission path without changing the original routing path.Through simulation studies and experiments,the outstanding performance of SPA and DPIOP in privacy preservation were demonstrated,with saving energy by about 63%,and reducing delay by about 35%.